Reclaiming evolution : a dialogue between Marxism and institutionalism on social change - Dugger, William M. (Advances in social economics., 2002)
Howard Sherman and William M. Dugger engage in a dialogue on social evolution from Institutionalist and Marxist perspectives, each representing one side. Together they explore the way society develops using the equally radical, but very different approaches of Thorstein Veblen and Karl Marx.